2007
DOI: 10.1080/09638280600919764
|View full text |Cite
|
Sign up to set email alerts
|

The development of a clinical practice stroke guideline for physiotherapists in The Netherlands: A systematic review of available evidence

Abstract: The guideline provides physiotherapists with an evidence-based instrument to assist them in their clinical decision making regarding patients with stroke. As most of the recommendations included in the guideline came from studies of patients in the post acute and chronic phase of stroke, and in general involved patients with less severe and uncomplicated stroke, more needs to be learned about the more complex cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 67 publications
1
67
0
6
Order By: Relevance
“…It was convincingly demonstrated and highlighted that exercise load is a highly important variable [27,51]. Exercise programmes would be more effective if they would be more intense, with a high frequency (twice weekly) and especially if the length of the programme would exceed 25 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…It was convincingly demonstrated and highlighted that exercise load is a highly important variable [27,51]. Exercise programmes would be more effective if they would be more intense, with a high frequency (twice weekly) and especially if the length of the programme would exceed 25 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies suffered from low treatment contrast; a valid comparison between the treatment and control groups was prohibited because often no control was implemented for the amount of attention given to both groups. Based on previous systematic reviews, Kwakkel et al 6 and van Peppen et al 23,56,57 found that the overall sizes of treatment effects were relatively small ranging from 5% 6 to maximally 12% 23 in favor of the experimental treatment arm. These relatively small effects further increase the risk of Type II error.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…14.350.047) and facilitated over a 1-year course in which all instructors were also trained to select and apply the core set of measurement instruments recommended by the Dutch stroke rehabilitation guidelines and to predict individual functional outcome. 57 This systematic review has highlighted many methodological shortcomings in the studies reviewed. Future RCTs need to analyze the content of therapy and consider the intensity of intervention delivered in relation to the outcomes achieved.…”
Section: Moving Forwardmentioning
confidence: 99%
“…17 Participants walked 10 metres quickly but safely, and the time was recorded from a standing start until participants had passed the 10-metre line with both feet. Two trials were performed, and the fastest time was recorded.…”
Section: Methodsmentioning
confidence: 99%